Being Moved: Louis XIV's Triumphant Tenderness and the Protestant Object. (2014) - Ibbett, Katherine
<x content-type="archive" xml:space="preserve">Abstract</x> This essay examines the place of affect in Le Triomphe de la Religion, a text from 1687 that praises Louis XIV for the Revocation of the Edict of Nantes and the forced conversion of French Protestants. It explores the role of the material object in this text and contrasts it with seventeenth-century Protestant fears about the seductive power of Catholic objects. Drawing on the work of affect theory, it suggest how attention to the strange relation between emotion and the material object might better illuminate our sense of what it meant to be religiously different in absolutist France.